9. Dual-Platform Products (PC and Mac) - Feist, David; Belyk, Diane (International Review of Research in Open and Distributed Learning, 2002)
Most of the other reports in this series have featured collaborative tools that were designed for use on PC-compatible platforms, and tested by our evaluation team on these platforms exclusively. This report reviews four integrated software products ensuring “interoperability” between the two major computing systems, PC-compatible and Macintosh. The products are compared in terms of their different levels of interoperability and complexity, as defined by the American Society for Training & Development (ASTD).